Social Media Exposure of Students in Relation to Academic Performance - T. Baria, Grazl (International Journal of Advanced Engineering, Management and Science, 2021)
This study aimed to determine the level of academic performance of college students in relation to their level of social media exposure. The descriptive-correlational research design was used. The study was conducted during the First Semester of 2018-2019 in CapSU Dayao Satellite College utilizing the 186 randomly selected 4th-year college students from the four curricular (4) programs. A researcher-made questionnaire was utilized. Gathered data were analyzed and interpreted using mean, standard deviation, t-test, One-way ANOVA, and Pearson r. Results revealed that the respondents were 18-20 years old age, females, and with family income below the poverty threshold level. Respondents’ level of social media exposure is “sometimes” and their academic performance is “good.” Further, no significant difference was found in the level of social media exposure when grouped according to sex and monthly income, however, a significant difference was found when grouped according to age. On the other hand, no significant difference was found in the respondents’ academic performance when grouped according to age, sex, and monthly family income. Further, no significant association or relationship was found between the level of social media exposure and the academic performance of the respondents. This implies that even though the respondents were exposed to social media they were able to maintain a good academic performance. Therefore, the time spent by students on the different social media platforms or the number of gadgets used is not indicative and determinant of how they will perform in their academics as a whole.